ASPEK HUKUM BERKEADILAN DALAM PELAYANAN KESEHATAN SECARA BERJENJANG DENGAN PEMBIAYAAN BPJS - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study examines the aspect of equitable justice in the tiered health care services provided by BPJS from a normative legal perspective through a comprehensive literature review. The main findings indicate that the strong constitutional foundation (1945 Constitution, Articles 28H and 34; SJSN Law No. 40 of 2004; BPJS Law No. 24 of 2011; Ministry of Health Regulation No. 16/2024) is undermined by discriminatory practices in Class 3 facilities, delays in emergency referrals, a ban on self-referrals, disparities in rural primary health care facilities (FKTP), and weak sanctions against partner hospitals. JKN financing via premiums from the PBI-APBN segment, salary-based PPU, fixed PBPU, and cross-subsidy mutual aid faces a deficit of Rp30 trillion (2026) due to a 111% claim ratio, moral hazard, and fraud, leading to delayed hospital claims and a decline in service quality for the poor. The study recommends strict regulatory oversight, real-time digital referral systems, progressive premiums, anti-fraud capitation, and benchmarking Thailand’s UCS for a Rawlsian-style inclusive JKN that provides protection.